Vortex-induced three-degree-of-freedom vibration of a piggyback circular cylinder system. (June 2022) - Chen, L.F.; Wu, G.X.
Abstract: A stabilized finite element method is adopted to solve the Navier–Stokes equations written in the arbitrary Lagrangian–Eulerian from. Extensive simulations are undertaken to investigate the vortex induced vibration characteristics of a piggyback circular cylinder system, or a smaller cylinder rigidly connected to a main one. In particular, the system is in three-degree-freedom motion, or its rotation motion is taken into account, while the previous work very much focuses on translational motions. This is achieved though using remeshing during the motion of the system. Various case studies have been undertaken at Reynolds number R e = 100, as the prime purpose is not about turbulence itself but the effect of rotation on the interaction of the piggyback cylinder system with the flow. Extensive results are provided to show the motion behaviours of the piggyback system at different orientation relative to the incoming flow. The effect of the rotational motion is extensively investigated. Key physical features are highlighted and conclusions are then drawn.